Viabilità relazionale: una prospettiva im/mobile delle relazioni nel Gambia transnazionale - Paolo Gaibazzi (EtnoAntropologia)
While anthropologists have long studied how mobility and immobility shape social relationships, this article describes relatedness itself as a form of im/mobility. It draws on ethnographic research among Soninke speakers in the Gambia and in the diaspora who express their relationship to others through images of what could be characterized as “viability”. The conceptual metaphor of viability serves to analyse three aspects of relational im/mobility. Firstly, viability hints at the infrastructural aspects, such as when Soninke speakers imagine kinship as a road or a network of roads connecting and channelling kinsfolk. Secondly, such relational paths are more or less viable, socially, affectively and economically, depending on whether related people travel either collectively or in a scattered fashion, either closer to or away from each other. Thirdly, viability captures the existential aspect of relatedness, for Soninke speakers also perceive others as entering, inhabiting and exiting their own lives and living condition.